Intestinal permeability and inflammation in patients on NSAIDs. Issue 4 (1st October 1998) - Sigthorsson, G; Tibble, J; Hayllar, J; Menzies, I; Macpherson, A; Moots, R; Scott, D; Gumpel, M J; Bjarnason, I
Abstract : Background —The frequency with which non-steroidal anti-inflammatory drugs (NSAIDs) increase small intestinal permeability and cause inflammation is uncertain. Aims —To examine small intestinal permeability and inflammation in a large number of patients on long term NSAIDs. Methods —Sixty eight patients receiving six different NSAIDs for over six months underwent combined absorption-permeability tests at three different test dose osmolarities (iso-, hypo-, and hyperosmolar). Two hundred and eighty six patients on 12 different NSAIDs underwent indium-111 white cell faecal excretion studies to assess the prevalence and severity of intestinal inflammation. Results —The iso- and hyperosmolar tests showed significant malabsorption of 3–0-methyl-d -glucose, d -xylose, andl -rhamnose. Intestinal permeability changes were significantly more pronounced and frequent with the hypo- and hyperosmolar as opposed to the iso-osmolar test. Sequential studies showed that four and nine patients (of 13) developed inflammation after three and six months treatment with NSAIDs, respectively. There was no significant difference (p>0.1) in the prevalence (54–72%) or severity of intestinal inflammation in the 286 patients taking the various NSAIDs apart from those on aspirin and nabumetone, these having no evidence of intestinal inflammation. There was no significant correlation between the inflammatory changes and age, sex, dose of NSAID, length of disease, or NSAID ingestion. Conclusions —Intestinal permeability test dose composition is an important factor when assessing the effects of NSAIDs on intestinal integrity. All the conventional NSAIDs studied were equally associated with small intestinal inflammation apart from aspirin and nabumetone which seem to spare the small bowel.